2014
DOI: 10.2134/fg-2013-0051-rs
|View full text |Cite
|
Sign up to set email alerts
|

A Survey Investigating Alfalfa Winter Injury in Minnesota and Wisconsin from the Winter of 2012‐2013

Abstract: The climate in the upper Midwest is noted for extreme weather events that greatly increase the risk of alfalfa (Medicago sativa L.) winter injury. An electronic survey was sent to alfalfa producers and crop consultants in Minnesota, Wisconsin, and Iowa with the goal of providing a retrospective assessment of the causes of alfalfa winter injury during the winter of 2012–2013. Almost all alfalfa producers who responded to the survey observed some winter injury, and a majority of crop consultants indicated more t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…and forage mass the following spring (Undersander et al, 2011;Wells et al, 2014). For these reasons, a fall cut was included for two of the 2015 cutting treatments to test the effects of a fall harvest on reduced lignin alfalfa cultivars.…”
Section: Methodsmentioning
confidence: 99%
“…and forage mass the following spring (Undersander et al, 2011;Wells et al, 2014). For these reasons, a fall cut was included for two of the 2015 cutting treatments to test the effects of a fall harvest on reduced lignin alfalfa cultivars.…”
Section: Methodsmentioning
confidence: 99%
“…Other studies reported a lack of T A B L E 5 Total forage dry matter yield in the post-sowing year of alfalfa initially planted with different companion crops in four environments at Sainte-Anne-de-Bellevue, QC, Canada consistency in the residual impact of annual companion crops used for alfalfa establishment on forage yields in post-sowing years (Sheaffer et al, 2014;Wiersma et al, 1999). This lack of consistency might be because alfalfa stem density in postestablishment years is related to multiple factors, including weather conditions, cultivar selection, and stand management (Wells, Martinson, Undersander, & Sheaffer, 2014). When compared with solo-sown alfalfa, yields of alfalfa established with a companion crop tended to vary not only from site to site but also from year to year, as many environmental factors could affect the results.…”
Section: Alfalfa Winter Survival and Yields In The Post-sowing Yearmentioning
confidence: 99%
“…In the northern Great Plains, alfalfa stand persistence and forage yield can be reduced due to winter-kill and winter-injury. In 2013, over 90% of alfalfa growers in Minnesota and Wisconsin reported winter-kill and winter-injury [12]. Most winter-kill happens when several weather factors such as above normal rainfall, lack of snow cover, and temperatures below −15 • C are combined [13].…”
mentioning
confidence: 99%